Silicon Improves Chilling Tolerance During Early Growth of Maize by Effects on Micronutrient Homeostasis and Hormonal Balances - Moradtalab, Narges; Weinmann, Markus; Walker, Frank; Höglinger, Birgit; Ludewig, Uwe; Neumann, Guenter (Frontiers in Plant Science, 2018)
Abstract Low soil temperature in spring is a major constraint for the cultivation of tropical and subtropical crops in temperate climates, associated with inhibition of root growth and activity, affecting early growth and frequently plant performance and final yield. This study was initiated to investigate the physiological base of cold-protective effects induced by supplementation with silicon (Si), widely recommended as a stress-protective mineral nutrient. Maize was used as a cold-sensitive model plant, exposed to chilling stress and low root-zone temperature (RZT) during early growth in a lab to field approach. In a pot experiment, two‒weeks exposure of maize seedlings to low RZT of 12-14°C, induced leaf chlorosis and necrosis, inhibition of shoot and root growth and micronutrient limitation (particularly Zn and Mn). These phenotypes were mitigated by seed treatments with the respective micronutrients, but surprisingly, also by Si application. Both, silicon and micronutrient treatments were associated with increased activity of superoxide dismutase in shoot and roots (as a key enzyme for detoxification of reactive oxygen species, depending on Zn and Mn as cofactors), increased tissue concentrations of phenolics, proline, and antioxidants, but reduced levels of H2O2. These findings suggest that mitigation of oxidative stress is a major effect of Zn, Mn and Si applied as cold stress protectants. In a soil‒free culture system without external nutrient supply, Si significantly reduced large leaching losses of Zn and Mn from germinating seeds exposed to low-temperature stress. Silicon also increased the translocation of micronutrient seed reserves to the growing seedling, especially the Zn shoot translocation. In later stages of seedling development (10 days after sowing), cold stress reduced the root and shoot contents of important hormonal growth regulators (indole acetic acid, gibberellic acid, zeatin). Silicon restored the hormonal balances to a level comparable with non‒stressed plants and stimulated the production of hormones involved in stress adaptation (abscisic, salicylic, and jasmonic acids). Beneficial effects of Si seed treatments on seedling establishment and the nutritional status of Zn and Mn were also measured for a field-grown silage maize, exposed to chilling stress by early sowing. This translated into increased final biomass yield.